3-pyridinylboronic acid ameliorates rotenone-induced oxidative stress through nrf2 target genes in zebrafish embryos - ALTURFAN, EBRU IŞIK; MEGA TİBER, PINAR (My University, 2022)
Parkinson\"s disease (PD) is one of the most common forms of neurodegenerative diseases and research on potential therapeutic agents for PD continues. Rotenone is a neurotoxin that can pass the blood-brain barrier and is used to generate PD models in experimental animals. Boron is a microelement necessary for neural activity in the brain. Antioxidant, non-cytotoxic, antigenotoxic, anti-carcinogenic effects of boric acid, the salt compound of boron has been reported before. Boronic acids have been approved for treatment by FDA and are included in drug discovery studies and pyridine boronic acids are a subclass of heterocyclic boronic acids used in drug design and discovery as substituted pyridines based on crystal engineering principles. The aim of our study was to determine the effect of 3-pyridinylboronic acid in rotenone-exposed zebrafish embryos, focusing on oxidant-antioxidant parameters and gene expression levels of nuclear factor erythroid 2-related factor 2 (Nrf2) target genes gclm, gclc, hmox1a, nqo1, and PD related genes, brain-derived neurotrophic factor, dj1, and tnfa alpha. Zebrafish embryos were exposed to Rotenone (10 mu g/l); Low Dose 3-Pyridinylboronic acid (100 mu M); High Dose 3-Pyridinylboronic acid (200 mu M); Rotenone + Low Dose-3-Pyridinylboronic acid (10 mu g/l + 100 mu M); Rotenone + High Dose-3-Pyridinylboronic acid (10 mu g/l + 200 mu M) in well plates for 96 h post-fertilization (hpf). Our study showed for the first time that 3-pyridinylboronic acid, as a novel sub-class of the heterocyclic boronic acid compound, improved locomotor activities, ameliorated oxidant-antioxidant status by decreasing LPO and NO levels, and normalized the expressions of bdnf, dj1, tnf alpha and Nrf2 target genes hmox1a and nqo1 in rotenone exposed zebrafish embryos. On the other hand, it caused the deterioration of the oxidant-antioxidant balance in the control group through increased lipid peroxidation, nitric oxide levels, and decreased antioxidant enzymes. We believe that these results should be interpreted in the context of the dose-toxicity and benefit-harm relationship of the effects of 3-pyridinylboronic.
Keywords: Sağlık Bilimleri; Yaşam Bilimleri; Temel Bilimler; Health Sciences; Life Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Clinical Medicine (MED); Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisciplinary; Parkinson's disease; Rotenone; 3-Pyridinylboronic acid; Zebrafish embryos; BORIC-ACID; BORON-COMPOUNDS; DIETARY BORON; BRAIN; METABOLITE; TOXICITY; SELENIUM; BORAX